METAPHYSICAL ASSUMPTIONS AND THEORETICAL STRUCTURES IN NATURAL SCIENCES: A SYSTEMATIC LITERATURE REVIEW ANALYSIS OF THE ONTOLOGICAL FOUNDATIONS OF NATURAL AND SOCIAL SCIENCES - Dewi Astuti; Insih Wilujeng; Woro Sri Hastuti; Ifan Awanda (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
assumptions underlying the theoretical structure of the Natural and Social Sciences (SPS), with a particular focus on the ontological foundations of both disciplines. This study uses a Systematic Literature Review (SLR) approach referring to the PRISMA 2020 protocol. A systematic literature search was conducted through the Scopus, SpringerLink, Taylor & Francis Online, PhilPapers, and MDPI databases, with a publication period of 2015–2026. Inclusion criteria included peer-reviewed journal articles, books, and book chapters that discuss metaphysical, ontological, epistemological, or methodological aspects of the natural and/or social sciences. A total of 29 key literatures were analyzed thematically using a narrative synthesis approach. The analysis revealed four main themes: (1) ontological assumptions in the natural sciences are characterized by metaphysical naturalism that emphasizes an orderly and observable external reality; (2) ontological assumptions in the social sciences exhibit greater diversity, encompassing critical realism that recognizes social structures as emergent, social constructivism, and an ontology of agency and structure; (3) ontological tensions between the natural and social sciences frequently arise in interdisciplinary research, particularly in the area of ​​sustainability, but critical realism and methodological pluralism are offered as potential resolutions; (4) an integrated naturalistic metaphysics (scientific metaphysics) is proposed as a framework that bridges scientific and social ontologies through a model-based approach and inference to the best explanation. The findings of this study provide a theoretical contribution to the development of social sciences as an interdisciplinary field, by offering a conceptual map of metaphysical assumptions that can facilitate more reflective and productive cross-disciplinary collaboration.